2013
DOI: 10.1590/s0100-29452013000200018
|View full text |Cite
|
Sign up to set email alerts
|

Severidade de doenças em maracujazeiro para identificação de fontes de resistência em condições de campo

Abstract: RESUMO -O objetivo deste trabalho foi utilizar uma escala de severidade para algumas doenças do maracujazeiro, visando à identificação de fontes de resistência. Foram avaliados 75 acessos de Passiflora spp. em condições de campo, sob alta infecção natural dos patógenos, para a severidade da virose, nas folhas (VIFO), frutos (VIFR) e distribuição na planta (VIPL), bem como para verrugose nos frutos e ramos (VEFR e VERA, respectivamente) e antracnose nos frutos (ANFR). Houve alta variabilidade para resistência à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 7 publications
2
31
0
3
Order By: Relevance
“…In this context, different authors have indicated the need for research focused on increasing the resistance of existing cultivars or on developing new cultivars using both intraspecific and interspecific crosses Meletti et al 2005;Faleiro et al 2005). The genetic variability and the gradient of resistance identified in this study reinforce the possibility, which was also presented by Oliveira et al (2013), of employing intraspecific crossing as a strategy to reduce the susceptibility of passion fruit cultivars to the primary diseases that affect passion fruit culture.…”
Section: Discussionsupporting
confidence: 80%
“…In this context, different authors have indicated the need for research focused on increasing the resistance of existing cultivars or on developing new cultivars using both intraspecific and interspecific crosses Meletti et al 2005;Faleiro et al 2005). The genetic variability and the gradient of resistance identified in this study reinforce the possibility, which was also presented by Oliveira et al (2013), of employing intraspecific crossing as a strategy to reduce the susceptibility of passion fruit cultivars to the primary diseases that affect passion fruit culture.…”
Section: Discussionsupporting
confidence: 80%
“…Among the factors that limit the productivity, the high incidence of disease is crucial because in general there are no varieties of yellow passion fruit with satisfactory resistance (MELETTI, 2011;OLIVEIRA et al, 2013). Among the diseases, it can be highlighted those caused by the fungus Fusarium oxysporum f. sp.…”
Section: H B Santos Et Almentioning
confidence: 99%
“…Fruits were collected randomly in the plot at the beginning of the maturation process and evaluated by grading scale (Junqueira et al, 2003;Oliveira et al, 2013). To evaluate viral disease in plants, assessments were performed considering the onset of symptoms on plants per plot using grading scale .…”
Section: Nunes De Jesus Et Al 2131mentioning
confidence: 99%